2002
DOI: 10.1136/ijgc-00009577-200201000-00003
|View full text |Cite
|
Sign up to set email alerts
|

High dose rate (HDR) cervical ring applicator to control bleeding from cervical carcinoma

Abstract: Grigsby PW, Portelance L, Williamson JF. High dose rate (HDR) cervical ring applicator to control bleeding from cervical carcinoma. Int J Gynecol Cancer 2002;12:18-21. The objective of this study was to evaluate the use of the high dose rate (HDR) cervical ring applicator to control acute cervical bleeding from carcinoma of the uterine cervix. This study consists of 15 patients presenting with invasive carcinoma of the uterine cervix with acute vaginal bleeding requiring transfusion. Initial irradiation, deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…There were two failures: one local failure and another distant combined with local failure (5) . For the treatment of hemorrhagic carcinoma of the uterine cervix, hemostatic radiotherapy is effective in controlling acute vaginal bleeding and can be delivered without undue acute or long‐term toxicity (2,3) . The current case demonstrated that radiation therapy can effectively control the vaginal bleeding from metastatic vaginal ASPS.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…There were two failures: one local failure and another distant combined with local failure (5) . For the treatment of hemorrhagic carcinoma of the uterine cervix, hemostatic radiotherapy is effective in controlling acute vaginal bleeding and can be delivered without undue acute or long‐term toxicity (2,3) . The current case demonstrated that radiation therapy can effectively control the vaginal bleeding from metastatic vaginal ASPS.…”
Section: Discussionmentioning
confidence: 71%
“…Radiation therapy can control vaginal bleeding by rapidly shrinking the tumor and sealing the oozing vasculature by fibrosis. Both external and intracavitary radiotherapy have been used for control of vaginal bleeding from uterine cervical cancer (2,3) . However, it is not well known whether radiation therapy can effectively control vaginal bleeding from a sarcoma of the female genital tract, especially from vaginal ASPS.…”
mentioning
confidence: 99%
“…This approach allows a majority of patients to proceed with subsequent external beam radiation therapy and even transition to curative treatment with long-term survival benefits due to favorable treatment outcomes. [7,8]…”
Section: Introductionmentioning
confidence: 99%
“…This approach allows a majority of patients to proceed with subsequent external beam radiation therapy and even transition to curative treatment with long-term survival benefits due to favorable treatment outcomes. [7,8] A systematic review and meta-analysis investigated the efficacy and toxic reactions of palliative radiation therapy in terms of pain relief and bleeding control in patients with advanced cervical cancer. The study summarized the hemostatic efficacy of high-dose-rate radiation therapy, whether delivered through external stereotactic body radiation therapy or ICBT.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article High dose rate (HDR) cervical ring applicator to control bleeding from cervical carcinoma by Grisgby et al . ( 1 ) The authors have addressed the use of HDR brachytherapy, in probably the first report in the literature, to control the bleeding from cervical cancer. The problem of vaginal bleeding requiring hemostatic radiotherapy is more frequently encountered in developing countries where the majority of cervical cancer patients present with bulky advanced diseases.…”
mentioning
confidence: 99%